La garantía de motivación bajo los estándares dogmáticos y jurisprudenciales en la actualidad como parte del derecho a la defensa en las sentencias penales. - Tapia Soria Kateryn Maricela (2025)
The following research aims to study the new standards of the guarantee of motivation as part of the criminal due process stipulated from the Ecuadorian constitutional and legal system, with the recent jurisprudential advances of the Ecuadorian Constitutional Court, where a radical change is reflected on this guarantee, which are far from the old “test of motivation” by the current motivational vices contemplated in the sentence No. 1158-17-EP/21, to establish whether in a specific case the guarantee of motivation has been violated or not. As for the development of jurisprudential lines by the high courts of Ecuador in order to comply with the current guidelines of modern dogmatics, the criteria are seen to be far from the previous "motivation test" since lines of motivation have been adopted under the legal argument. When a guiding criterion is violated, legal argumentation suffers from a motivational deficiency, and this is divided into three basic types: 1. nonexistence, 2. insufficiency, and 3. appearance. Therefore, the guarantee of motivation can correspond to any of these basic types. The role of the Ecuadorian Constitutional Court has been a determining factor in this jurisprudential development of the guarantee of motivation. Through its development, it has established new guidelines for a judicial decision to be considered reasoned. It has therefore moved toward adopting modern doctrine guidelines on legal argumentation to consider motivational defects, especially when it comes to a judgment that either condemns or confirms innocence within a criminal proceeding. Undoubtedly, the scope of this guarantee is crucial for a person who has received a conviction or a verdict confirming their innocence, since in a criminal proceeding, the victim also requires a reasoned decision. This research aims to verify V 5 the current level of motivation that judges have when issuing a sentence in a given case, and how the guarantee of motivation as part of criminal due process influences this type of decision within the new motivational standards of Ecuadorian jurisprudence and current relevant dogmatics. For the development of this research, a qualitative approach will be chosen since it is a bibliographic research, as well as qualitative methods and instruments such as the interview and document review guide, so that the current doctrine can be reviewed regarding the guarantee of motivation within the criminal process, as well as the jurisprudential contributions of the high courts, and the contributions of justice operators to comply with the objectives set out in the research. KEY WORDS: Motivation, Judgment, Due Process, Motivational defects.